EFFICACY OF PHACOEMULSIFICATION AND PHACOEMULSIFICATION COMBINED WITH GONIOSYNECHIALYSIS IN SURGICAL TREATMENT OF CHRONIC ANGLE-CLOSURE GLAUCOMA: 2-YEARS STUDY - Igor Novytskyy; Rostyslav Lopadchak (Acta Medica Leopoliensia)
Aim. To study the degree of angle opening and the decrease of intraocular pressure in primary angle-closure glaucoma (PACG) after cataract phacoemulsification and cataract phacoemulsification with goniosynechialysis (phaco + GLS).